15. Evaluation of Retained Immunity for Tetanus-Diphtheria and Pneumococcal Vaccines in Recipients of Cellular Therapies. (4th December 2021) - Angelidakis, Georgios; Chemaly, Roy F; Kebriaei, Partow; Ajami, Nadim J; Bhatti, Micah M; Shpall, Elizabeth; Hosing, Chitra; Jain, Preetesh; Mahadeo, Kris Michael; Khawaja, Fareed; Wargo, Jennifer; Jenq, Robert; et al.
Abstract: Background: Infectious complications in cancer patients (pts) who have received T-cell therapies are similar to those in autologous hematopoietic stem cell transplant (HCT) recipients, who - because they lose prior acquired immunity after undergoing conditioning regimens and transplantation- may be at an increased risk for vaccine-preventable infections. We sought to determine seroprotection rates against pneumococcus and tetanus-diphtheria before and after cellular therapies. Methods: In this ongoing prospective observational cohort study, we enrolled pts with any type of cancer who received cellular therapy with chimeric antigen receptor modified T cell (CAR-T), natural killer CAR-T, or T-cell receptor- directed immunotherapies at MD Anderson Cancer Center from January 2020 through May 2021. We performed antibody assays for diphtheria, tetanus, and pneumococcus before, at 1 month, and between 3-6 months after T-cell therapy for each pt regardless of vaccination history. Results: Of 38 pts enrolled, 27 (71%) were men and 25 (66%) had non-Hodgkin lymphoma (Table 1); 38 (100%) and 17 (45%) had a history of previous diphtheria-tetanus-acellular pertussis (Tdap) and pneumococcal vaccination, respectively (Table 2). Tetanus serologies were positive for all pts tested before, at 1 month and 3-6 months after T cell therapy (37/37 [100%], 22/22 [100%], and 13/13 [100%], respectively). Diphtheria serologies were positive for most pts tested before, at 1 month and 3-6 months after therapy (35/37 [95%], 20/22 [91%], and 11/13 [85%], respectively]. Pneumococcal serologies were positive for 8 out of 37 [22%] pts before therapy, among these 8 pts, 4 had positive serologies 1 month after therapy, and 2 of 3 tested 3-6 months after therapy had positive serologies. One pt received a pneumococcal vaccine 10 months after therapy but had negative serologies post-vaccination. Conclusion: Most pts who received T-cell therapy retained their immunity for diphtheria and tetanus, but most also lost their immunity for pneumococcus. This suggests that the standard of care for pts receiving T-cell therapy should include more robust strategy for pneumococcal vaccination, but its timing, need for booster dosing, and antibody response needs to be determined in future trials. Disclosures: Roy F. Chemaly, MD, MPH, FACP, FIDSA, AiCuris (Grant/Research Support)Ansun Biopharma (Consultant, Grant/Research Support)Chimerix (Consultant, Grant/Research Support)Clinigen (Consultant)Genentech (Consultant, Grant/Research Support)Janssen (Consultant, Grant/Research Support)Karius (Grant/Research Support)Merck (Consultant, Grant/Research Support)Molecular Partners (Consultant, Advisor or Review Panel member)Novartis (Grant/Research Support)Oxford Immunotec (Consultant, Grant/Research Support)Partner Therapeutics (Consultant)Pulmotec (Consultant, Grant/Research Support)Shire/Takeda (Consultant, Grant/Research Support)Viracor (Grant/Research Support)Xenex (Grant/Research Support) Fareed Khawaja, MBBS, Eurofins Viracor (Research Grant or Support) Ella Ariza Heredia, MD, Merck (Grant/Research Support)